2013
DOI: 10.1111/cfs.12099
|View full text |Cite
|
Sign up to set email alerts
|

Internationally adopted children's general and adoption‐specific stressors, coping strategies and psychological adjustment

Abstract: A B S T R AC TWe examined stress, coping and psychological adjustment of 68 children, aged 8-12, who were internationally adopted to Spain. Using the Kidcope, all children were asked about the most stressful general and adoption-related problem they experienced and the use and effectiveness of various coping strategies when dealing with the problem. For all reported problems, the nature of the problem (personal, interpersonal, regarding others), the content, the degree of stress it created and its perceived co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 44 publications
1
2
0
Order By: Relevance
“…These results suggested that institutionalized adolescents use the most useful strategies and this can be a predictor of positive psychological adjustment. This result was consistent with (36) who found that the most commonly used strategies by internationally adopted children are cognitive restructuring, problem solving, wishful thinking, express emotion, and social support more frequently.…”
Section: Part Iii: Coping Strategies Of Institutionalized Adolescentssupporting
confidence: 90%
“…These results suggested that institutionalized adolescents use the most useful strategies and this can be a predictor of positive psychological adjustment. This result was consistent with (36) who found that the most commonly used strategies by internationally adopted children are cognitive restructuring, problem solving, wishful thinking, express emotion, and social support more frequently.…”
Section: Part Iii: Coping Strategies Of Institutionalized Adolescentssupporting
confidence: 90%
“…Reluctance on the part of children to reveal their adoptive status to peers may be due in part to previous experiences of a negative reaction following disclosure. Several studies have reported how negative reactions to adopted status manifest in peers’ responses, including teasing, jokes, intrusive questioning and rejection (Baden, 2016; Neil, 2012; Reinoso et al, 2016). Despite a growing acceptance of adoption as way of forming a family, negative sociocultural interactions still occur for adopted individuals and families (Garber, 2020), and may contribute to misunderstandings and misperceptions of adoption.…”
Section: Adoptive Communicative Opennessmentioning
confidence: 99%
“…Although most adoptees seem to eventually adjust well to these preplacement hardships, adopted children continue to be overrepresented in mental health settings (Brodzinsky, 1990;Juffer & van Ijzendoorn, 2005), and some con icting results persist regarding the reparative effect the adoption itself may have on these outcomes (Brodzinsky et al, 2022). Adoptive parenthood appears to positively contribute to adopted children's emotional and behavioral development (Askeland et al, 2017;Finet et Reinoso et al, 2013). However, few research has been done on the mechanisms through which this impact occurs, and none considers the potential role of adoptive parents' attachment orientations, self-compassion and mindful parenting in adoptees' adjustment.…”
Section: Introductionmentioning
confidence: 99%